Land subsidence along the Beijing-Tianjin high-speed railway before and after the South-to-North water diversion project with multi-source monitoring datasets - Liu, Shaomin; Bai, Mingzhou (Frontiers in Earth Science, 2024)
The development of land subsidence has seriously affected the safe operation of Beijing-Tianjin high-speed railway. The South-to-North Water Diversion Project Central Route (SNWDP-CR) has provided conditions for controlling land subsidence in Beijing. In this paper, the time-series interferometric data, in-situ monitoring data of recent 20 years and the basic geological datasets are combined to analyze the changes of groundwater level and land subsidence along the railway before and after the SNWDP-CR. The effects of the Quaternary sedimentary, groundwater exploitation and soil deformation of different lithology on land subsidence along the railway under the new water conditions are revealed. The main conclusions are as follows: (1) The serious land subsidence area along the Beijing-Tianjin high-speed railway always concentrated in the section of DK11-DK23. After the operation of SNWDP-CR, the land subsidence along the railway generally showed a slowing trend. The maximum subsidence rate was reduced from 80mm/yr to 49mm/yr. The length of subsidence rate that more than 50 mm/yr of the section was reduced from 8.0 km to 0 km. (2) The groundwater level of different aquifer groups along the Beijing-Tianjin high-speed railway rose and declined before and after the SNWDP-CR. in eastern part of the plain, the groundwater level of each aquifer group has changed from a continuous decline (range 0.13-1.82 m) to a gradual rise (range 0.45-1.87 m) since 2017. However, in the southeast of the plain, the groundwater level still showed a continuous decline trend, with an average annual decline of 1.2-1.8m. (3) From 2006 to 2019, the subsidence of the first, second and third compression layer group along the railway accounted for 2.71%, 28.29% and 69%, respectively. The third compression layer group had the largest subsidence proportion and was the main subsidence layer. (4) The land subsidence along the Beijing-Tianjin high-speed railway is controlled by the basement structure. The difference of groundwater exploitation intensity led to differences in the spatial distribution of land subsidence along the railway. The subsidence of the soil layer below the bearing layer (about 50m) of the high-speed railway pile foundation exhibited the characteristics of viscoplastic or viscoelastic plasticity deformation.